2018
DOI: 10.1590/s0102-865020180010000003
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dexmedetomidine against myocardial ischemia-reperfusion injury in rabbits

Abstract: 1 AbstractPurpose: To investigate the influence of dexmedetomidine on myocardial ischemiareperfusion injury (IRI) in rabbits. Methods: Twenty-four New Zealand white rabbits were randomly divided into two equal-sized groups: IRI group (group IR) and dexmedetomidine group (group D). Systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP), left ventricular diastolic pressure (LVDP), +dp/ dtmax, -dp/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…TNF-α and IL-1β are responsible for the stimulation of chemokines and the secretion of adhesion molecules in ischemic tissues, and IL-6 is responsible for the regulation of inflammation ( 37 , 38 ). Previous studies have reported that Dex induces multiple protective effects on MIRI ( 39 ), and such findings were further supported by the present study. Yu et al ( 40 ) have reported that microRNA-665 and Dex protect cardiomyocytes against I/R injury caused by oxide stress and suppress apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…TNF-α and IL-1β are responsible for the stimulation of chemokines and the secretion of adhesion molecules in ischemic tissues, and IL-6 is responsible for the regulation of inflammation ( 37 , 38 ). Previous studies have reported that Dex induces multiple protective effects on MIRI ( 39 ), and such findings were further supported by the present study. Yu et al ( 40 ) have reported that microRNA-665 and Dex protect cardiomyocytes against I/R injury caused by oxide stress and suppress apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Dexmedetomidine is an alpha-adrenergic receptor agonist drug and extensively used as a sedative. Dexmedetomidine protects against myocardial infarction [125], ischemic brain [126] and kidney injury [127]. Previous studies have shown that preconditioning with Dex in rats has a protective effect on the renal function after I-R through the inhibition of the Janus kinase/signal transducers and activators of the transcription (JAK/STAT) signaling pathway [128].…”
Section: Other Anesthetics In Irimentioning
confidence: 99%
“…Dex is widely used in clinical scenarios and recent studies have indicated that the use of Dex is advantageous in reducing anesthetic requirements and enhancing hemodynamic stability following cardiac surgery (6). Dex pre-conditioning and Dex perfusion during the whole surgery have been examined in a variety of animal models of ischemia-reperfusion and have been demonstrated to protect multiple organs and provide a protective effect against MIRI (7)(8)(9). Furthermore, clinical study have suggested that Dex perfusion during the whole cardiac surgery under CPB reduces the risk of postoperative MIRI (10).…”
Section: Introductionmentioning
confidence: 99%